Pengaruh Penggunaan Gadget Terhadap Perkembangan Moral Siswa Pada Mata Pelajaran Akidah Akhlak Ma Asy-Syari’ah - Rima Erviana; Mulyawan Safwandy Nugraha (Jurnal Pendidikan Indonesia (JOUPI), 2023)
This study aims to find out (1) a description of students' use of Gadgets in the Aqidah Akhlak subject of MA Asy-Syari'ah (2) an overview of the Moral Development of MA Asy-Syari'ah students and (3) the effect of using Gadgets on the moral development of MA Asy Students - Shari'ah Waluran. This type of research is quantitative research using the ex-post facto method. The research was conducted at MA Asy-Syari'ah Waluran, Kab. Sukabumi. In this study, the population was 112 students of MA Asy-Syri'ah. And taking samples using random sampling technique with a total sample of 24 students. The data collection technique was carried out using an instrument on the Gadget usage scale and the student moral development scale. The data analysis technique used is descriptive statistics to answer the problem formulation and inferential statistics using a simple regression test. Based on the results of descriptive statistical analysis, the use of gadgets has a mean value of 81.41, while moral development has a value of 84.08. The results of a simple regression (inferential statistics) obtained an R2 value of 0.155 or in the form of a percentage of 15% and the remaining 85% was influenced by variables not involved in this research. This means that there is an influence between the use of gadgets and the moral development of MA Asy-Syari'ah Waluran students. Based on the significant test to analyze inferential statistics, the value of 0.008 <0.05 strengthens the hypothesis that the use of gadgets affects the moral development of MA Asy-Syari'ah Waluran students.